Measurement of fidgeting in patients with anorexia nervosa using a novel shoe-based monitor. (January 2017) - Belak, Lauren; Gianini, Loren; Klein, Diane A.; Sazonov, Edward; Keegan, Kathryn; Neustadt, Esther; Walsh, B. Timothy; Attia, Evelyn
Abstract: Objective: To objectively assess seated non-exercise physical activity in patients with anorexia nervosa (AN) relative to healthy controls (HCs) and examine the associations between this physical activity, eating disorder pathology, and levels of anxiety and depression. Method: Eleven inpatients with AN and 10 HCs wore a shoe-based accelerometer (SmartShoe) at three time points: a) while eating lunch, b) filling out questionnaires, and c) watching television for 1 h. Results: Across all three tasks, patients with AN were significantly more active than HCs, thereby engaging in a greater degree of restless or fidgeting behavior. Degree of physical activity was positively correlated with eating disorder psychopathology in the sample with AN, and a trend towards a positive association between physical activity and levels of depression and anxiety was also found in this sample. Among individuals with AN, physical activity was not significantly correlated with BMI, duration of illness, or number of days since hospital admission. Discussion: Use of a minimally invasive, shoe-based monitor revealed patients with AN engaged in a greater degree of fidgeting relative to HCs during quiet, seated tasks and this heightened activity was related to measures of pathology. Non-exercise physical activity, including fidgeting, may warrant further clinical attention in this patient population. Highlights: Non-invasive objective measurement of fidgeting in patients with anorexia nervosa Patients with anorexia nervosa are more restless than healthy controls while seated. Worsening eating disorder pathology is correlated with heightened restlessness.